An overview of the digital publishing market in Baltic countries (Estonia, Latvia and Lithuania) (Libellarium: journal for research in the field of information and related sciences, 2014)
The aim of this paper is to analyze several aspects of digital publishing markets in Baltic countries. Estonia, Latvia and Lithuania have their own languages, so there are three different publishing markets. Results show that there are significant differences in the number of available titles, despite the fact that the Baltic e-book market is relatively new. The research on e-book sales identified the main e-book retailers and publishers in Baltic countries. E-books in Lithuanian, Latvian and Estonian available on sale were counted and the differences between e-book formats and the pricing in each country were established. The results showed that the smallest Baltic country, Estonia, has more e-books on sale than both Latvia and Lithuania. It is difficult to say if Latvia even has an e-book market at all. Lithuania is somewhere in the middle. Finally, an overview of the largest retailers and publishers is provided and overall publishing dynamics within the past 20 years is described.
Keywords: digital publishing; e-books; digital books; e-book stores; e-book retailers; e-book publishers; Baltic countries; Estonia; Latvia; Lithuania